2015
DOI: 10.1002/erv.2383
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological and Behavioural Short‐Term Effects of Cognitive Remediation Therapy in Adolescent Anorexia Nervosa: A Pilot Study

Abstract: Results suggest that CRT may be beneficial for enhancing flexibility in adolescents with AN. However, randomized controlled studies are essential to determine the actual efficacy of this intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 30 publications
1
26
2
1
Order By: Relevance
“…Some studies revealed that adolescents with AN showed no inefficiencies in setshifting compared with controls, whereas adults with a longer AN history had clear weaknesses (Fitzpatrick et al, 2012;Kjaersdam Telleus et al, 2015;McAnarney et al, 2011;Shott et al, 2012;van Noort, Pfeiffer et al, 2016b). The results for central coherence in children and adolescents are largely the same with some researchers reporting poorer performances on tasks requiring global processing strategies (Allen et al, 2012;Lang et al, 2015), while others find no differences compared with healthy controls (van Noort, Kraus et al, 2015a). The results for central coherence in children and adolescents are largely the same with some researchers reporting poorer performances on tasks requiring global processing strategies (Allen et al, 2012;Lang et al, 2015), while others find no differences compared with healthy controls (van Noort, Kraus et al, 2015a).…”
Section: Discussionmentioning
confidence: 96%
“…Some studies revealed that adolescents with AN showed no inefficiencies in setshifting compared with controls, whereas adults with a longer AN history had clear weaknesses (Fitzpatrick et al, 2012;Kjaersdam Telleus et al, 2015;McAnarney et al, 2011;Shott et al, 2012;van Noort, Pfeiffer et al, 2016b). The results for central coherence in children and adolescents are largely the same with some researchers reporting poorer performances on tasks requiring global processing strategies (Allen et al, 2012;Lang et al, 2015), while others find no differences compared with healthy controls (van Noort, Kraus et al, 2015a). The results for central coherence in children and adolescents are largely the same with some researchers reporting poorer performances on tasks requiring global processing strategies (Allen et al, 2012;Lang et al, 2015), while others find no differences compared with healthy controls (van Noort, Kraus et al, 2015a).…”
Section: Discussionmentioning
confidence: 96%
“…However, this analysis may have been compromised because of two studies from the same research group using overlapping samples (Herbrich et al, 2017;van Noort et al, 2016). However, the meta-analysis of common outcome measures indicated small effect size improvements in central coherence following CRT for individuals, suggesting that YP exhibited a gestalt information processing style following CRT.…”
Section: Discussionmentioning
confidence: 99%
“…A within-subjects design showed that significant improvements on neurocognitive measures were found in a child and adolescent inpatient population with AN after undergoing an eight-session CRT program (54). Compared to HCs, adolescents with AN (n=20) demonstrated improved cognitive flexibility on neuropsychological measures following CRT, although improvements in self-reported flexibility (as measured by the Cognitive Shift and Behavioral Shift subscales of the Behavioral Rating Inventory for Executive Functioning, BRIEF-SR) and central coherence (as measured by copy condition of the Rey-Osterrieth Complex Figure Test) did not differ between the two groups (55). Although no empirical data were reported, a small sample of inpatient adolescents with AN found a group-based CRT program to be fun, playful, and engaging (56).…”
Section: Treatments Targeting Neurocognitive or Executive Function Inmentioning
confidence: 96%